The Effect Of Twitter Application Teaching Media To The Reading Comprehension Of Grade Nine Students Of Smp Negeri 4 Pematang Siantar On A News Item Text - Nopaulina Sinaga; Sanggam Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the effect of the Twitter application as a teaching medium on ninth grade students' reading comprehension of the News Item text. This research was carried out at SMP Negeri 4 Pematang Siantar, namely in classes IX-3 and IX-4. The formulation of the research problem is the influence of the Twitter application as a teaching medium in reading news item texts for class IX students at SMP Negeri 4 Pematang Siantar. Researchers used quantitative methods with a quasi-experimental design and used two classes, namely the experimental class and the control class. Data collection was carried out using multiple choice tests. The instruments used to collect data were taken from students' pre-test and post-test results; scores were then calculated and analyzed using MS Excel and manual The research results showed that the average score of the experimental class was a pre-test score of 57.96 and a post-test score of 80.8. Meanwhile, the average score for the control class was a pre-test score of 61.09 and a post-test score of 71.40. The results of student scores on the post-test show that the use of Twitter learning media is very effective in reading news item texts for class IX students. The t-test calculation shows that the t-test value is greater than the ttable value (2.13 > 1.669). at a significance level of 5%, a two-sided test means the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This means that the influence of the Twitter application as a teaching medium can improve students' reading comprehension